INSTITUTIONAL, SOCIETAL, AND TEACHER FACTORS ON THE IMPLEMENTATION OF AN ENGLISH COURSE IN GARUT: A QUALITATIVE STUDY - Sinta Dewi (Institut Pendidikan Indonesia Garut, 2021)
Unreached agreement on the educational goals often arises among stakeholders due to the fact that most of the program goals were designed intuitively by either the instructors or institution without taking into account the learners‟ needs and the larger context in which the program takes place. This study intends to analyse the three situational factors: institutional, societal and teacher factors that may affect the implementation of one of the English courses in Garut. To this end, the present study employed case study design and used observation and semi-structured interview to collect the data. The findings indicated that the institutional factors such as facilities and supportive learning environment play an important role on the attainment of the teaching and learning goals. The society has expectation on the course to produce students with good communication skill. Meanwhile, the instructors were found to have different beliefs on what was percieved to be the best teaching practices (Genre Based Approach, Oral Approach and Fluency Activity Approach). More comprehensive aspects of the factor are recommended to be explored in further research.